Social Interaction and Local Wisdom as Drivers of Leadership and Competitive Advantage - Maklassa, Dg.; Nurbaya, Sitti (Jurnal Minds: Manajemen Ide dan Inspirasi, 2025)
This study examines how social interaction, local wisdom, and institutional forces jointly shape leadership and competitive advantage in organizational settings. The central contribution lies in demonstrating that competitive advantage is not solely the outcome of structural resources but also of culturally embedded practices and relational dynamics. Using a quantitative approach, data were collected from 311 respondents drawn purposively from a population of 1,398 civil servant professionals and analyzed with SmartPLS 4.0. Measurement models confirmed validity and reliability, while structural models tested hypothesized causalities. Results reveal that social interaction and local wisdom significantly enhance both leadership and competitive advantage, whereas institutional factors influence competitive advantage but not leadership. Leadership itself strongly drives competitive outcomes. These findings position socio-cultural capital as a critical complement to institutional design, underscoring that sustainable advantage arises from leaders who embed local wisdom and social interaction into strategic practices.